Implementation of Multidisciplinary PAI in PAUD and SD - Evi Nurhalimah; Nurlaela; Farida Isroani; Fahmi Khumaini; Ahmad Manshur (al-Afkar, Journal For Islamic Studies, 2024)
Religious education received from an early age will have an influence on the child's subsequent religious development. The aim of this research is to determine the curriculum and implementation of PAI in PAUD and SD. This panel research is qualitative research using the library research method. The results obtained from this research are that the PAI PAUD Curriculum seeks to develop children's religious and spiritual potential, including an introduction to Allah through His nature and creation, Kalimah Tayyibah which reflects everyday Islamic values such as alhamdulillah and astaghfirullah and an introduction to the fifth pillar of Islam. This competency is described in a number of learning outcome indicators covering faith, morals and worship. The implementation of Islamic religious and moral values in students tends to lead to habits in daily behavior at school. The application of Islamic religious education in PAUD can also be carried out by teaching children morals, praying fardhu prayers properly and correctly, training children to learn the Koran with Iqro. The PAI curriculum content in elementary schools has 5 scopes of material contained in PAI subjects for grades I to VI, with the distribution as follows; Koran, 11 KD; Aqidah, 17 KD; Morals 25 KD, Fiqh, 12 KD; and History of Islamic Civilization (SPI), namely 33 KD. Implementation of the PAI curriculum includes planning, implementation and evaluation.